2002
DOI: 10.1046/j.1365-2109.2002.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Fillet shelf-life of Atlantic halibut Hippoglossus hippoglossus L. fed elevated levels of α -tocopheryl acetate

Abstract: Fish fillet quality may be influenced by the antioxidant level in preslaughter diet. Thus, the effects of dietary a-tocopheryl acetate supplementation and feeding time on the flesh quality of farmed Atlantic halibut Hippoglossus hippoglossus L. were investigated. Halibut of mean initial weight of 312 + 12.3 g were divided into two groups and fed commercial diets, supplemented with different levels of a-tocopheryl acetate at the dietary inclusion levels of 189 and 613 mg kg À1 diet. Fish were sampled after 6,9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
33
3
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 30 publications
8
33
3
5
Order By: Relevance
“…High vitamin E content in tissues would inhibit tissue lipid peroxidation (MURATA & YAMAUCHI 1989, FRIGG et al 1990, SAU et al 2004. Similar trends have been reported in rainbow trout (FRIGG et al 1990), turbot (STEPHAN et al 1995, sea bass (GATTA et al 2000), and Atlantic halibut (RUFF et al 2002). These reports indicated that the higher vitamin E consumption by the fish, the greater vitamin E concentrations in fish tissue, thus resulted in lower lipid peroxidation.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…High vitamin E content in tissues would inhibit tissue lipid peroxidation (MURATA & YAMAUCHI 1989, FRIGG et al 1990, SAU et al 2004. Similar trends have been reported in rainbow trout (FRIGG et al 1990), turbot (STEPHAN et al 1995, sea bass (GATTA et al 2000), and Atlantic halibut (RUFF et al 2002). These reports indicated that the higher vitamin E consumption by the fish, the greater vitamin E concentrations in fish tissue, thus resulted in lower lipid peroxidation.…”
Section: Discussionsupporting
confidence: 73%
“…It is known that vitamin E show antioxidant characteristics to the oxidants in the cell membrane and another compound in the structure of propolis, caffeic acid phenethyl ester (CAPE), blocks the production of reactive oxygen types (SEVEN et al 2010, HOSNUTER et al 2004. Vitamin E (␣-tocopherol) function as biological antioxidants to protect cellular macromolecules (DNA, protein, lipids) and other antioxidant molecules from uncontrolled oxidation by free radicals during normal metabolism or under the conditions of oxidative challenge such as infection, stress, and pollution (HUANG & HUANG 2004, RUFF et al 2002. Survival of fish fed the vitamin E supplemented diets was higher in general.…”
Section: Discussionmentioning
confidence: 99%
“…Fillet ctocopherol concentration was also increased at the highest level of NSVE supplementation, probably because minute amounts of this compound occurred as an impurity in the NSVE product used. Linear regressions of mean fillet a-tocopherol concentrations (standardized to fillet dry matter) versus as-fed dietary vitamin E concentration revealed diet-to-fillet transfer greater than reported for SYNE in other aquatic species (Stéphan et al 1995;Ruff et al 2002;Chaiyapechara et al 2003). The increased potency of NSVE is associated with superior binding of RRR-a-tocopherol to hepatic a-tocopherol transport protein (a-TTP) and therefore greater retention of RRR-a-tocopherol compared with its racemates or other tocopherol isomers (Stone and Papas 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Tocopherols prevent free radical oxidation of lipids and fatty acids in vivo (Bell et al 2000); postslaughter, they can reduce rates of oxidation and lengthen shelf life of fresh or frozen fillets (Gatta et al 2000;Ruff et al 2002;Hamre et al 2004). Tissue a-tocopherol content and oxidative stability have been enhanced via dietary supplementation with SYNE in sunshine bass (Kocabas and Gatlin 1999), rainbow trout Oncorhynchus mykiss (Chaiyapechara et al 2003), European seabass Dicentrarchus labrax (Gatta et al 2000), Atlantic salmon (Hamre et al 1998(Hamre et al , 2004Scaife et al 2000), Atlantic halibut Hippoglossus hippoglossus (Ruff et al 2002(Ruff et al , 2004, and turbot Scophthalmus maximus (Ruff et al 2003(Ruff et al , 2004. Although no significant differences were noted after long-term storage, fillet aldehydes numerically decreased with increasing dietary NSVE but not with ethoxyquin.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (2004), em estudos realizados com salmões (Oncorhynchus kisutsh), relataram taxas de crescimento semelhantes entre os peixes alimentados com 100 mg kg -1 de vitamina E e o grupo controle. Já Ruff (2002) não observou diferença de crescimento entre os tratamentos com 189 e 613 mg kg -1…”
Section: Resultsunclassified